Neighborhood Sustainable Development Approach in Tehran Metropolitan Case study: Bahar Neighborhood, Region 7 - zohreh fanei; fared saremei (جغرافیا و توسعه, 2014)

(untitled)
Neighbourhood development in the form of a participation, democratic and people based process from several decades ago in developed countries has been emphasized as the axis of urban sustainable development and metropolis areas. Tehran metropolis is facing with frequent problems regarding the optimum  management of spatial organization; and the present approach in its macro and centralized management has not been led to  urban sustainable development due to lack of reliance  on local solutions, participation of people, sustainable ecological local systems and therefore unsuccessful in preparing  basic needs of people.  Therefore, development of urban neighbourhood has been known as the starting point for development of urban sustainable management of Tehran metropolis. The final goal of sustainable neighbourhood development is people and provision of their first and necessary requirements with respect to their life environment. Thus, the present research through emphasizing on this aim, has sought to understand and test the new approach of neighbourhood development in modern urban management system, in one of urban neighbourhoods of Tehran metropolis. Therefore, this research has obtained some results in the framework of one thesis that basic change in planning structures of urban neighbourhood development with emphasis on neighbourhood system can lead to ecological socio-economical and cultural sustainability in Tehran’s neighbourhoods. Instability in the present conditions decreases greatly the index of local dependency among the people of Bahar neighbourhood. Decrease of this index causes the  local people to feel no responsibility against the under progress programs and the future programs, in other words, the attempt for increasing and generalization of the life quality index in different parts of the district will be decreased, therefore the development methods dominant on Bahar neighbourhood has no compatibility with the realization conditions of sustained development in local surface and planning for making fundamental changes and moving toward local sustainability is essential.